2022
DOI: 10.3390/ma15041430
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network-Based Multi-Objective Optimization of Adjustable Drawbead Movement for Deep Drawing of Tailor-Welded Blanks

Abstract: To improve the formability in the deep drawing of tailor-welded blanks, an adjustable drawbead was introduced. Drawbead movement was obtained using the multi-objective optimization of the conflicting objective functions of the fracture and centerline deviation simultaneously. Finite element simulations of the deep drawing processes were conducted to generate observations for optimization. The response surface method and artificial neural network were used to determine the relationship between variables and obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…They also improve the drawing quality in the mechanical deep drawing processes. 35,36 During the mechanical pre-bulging process, a decrease in force was observed due to the increase in the entrance angle, the easier flow of the sheet into the die cavity, and the prevention of the formation of wrinkles beforehand. It was observed that the forming forces during the forming process tended to decrease with an increase in the die entrance angle.…”
Section: Resultsmentioning
confidence: 99%
“…They also improve the drawing quality in the mechanical deep drawing processes. 35,36 During the mechanical pre-bulging process, a decrease in force was observed due to the increase in the entrance angle, the easier flow of the sheet into the die cavity, and the prevention of the formation of wrinkles beforehand. It was observed that the forming forces during the forming process tended to decrease with an increase in the die entrance angle.…”
Section: Resultsmentioning
confidence: 99%
“…The forming limit curves determined in the experimental tests were based on the modified Marciniak test. The displacement was determined by image analysis (stochastic network) [17,18].…”
Section: Forming Limit Curvesmentioning
confidence: 99%